2023
DOI: 10.1136/bmjopen-2023-073796
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum stress in the first 6 months after delivery: a longitudinal study in Nantong, China

Yanchi Wang,
Jian Gu,
Yuehong Gao
et al.

Abstract: ObjectivesThe objective is to to explore the longitudinal change trajectories of postpartum stress and its related factors.DesignA longitudinal study with follow-ups from 42 days to 6 months after delivery.Settings and participantsA total of 406 postpartum women were recruited at baseline (42 days after delivery) from 6 hospitals in Nantong, Jiangsu Province, China, and followed up at 3 and 6 months. After the follow-ups, 358 postpartum women were retained for further analysis.MethodsPostpartum stress was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 86 publications
0
4
1
Order By: Relevance
“…The correlations were found to be nonstatistically significant, ranging from −0.15 to −0.02. Conversely to our findings, Wang et al [3] found associations between age, education levels (including paternal) and high BMI with all the dimensions of the MPSS. This may be due to sample size differences (167 vs. 406) or the specificity of the population of the study (Spanish-speaking women).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The correlations were found to be nonstatistically significant, ranging from −0.15 to −0.02. Conversely to our findings, Wang et al [3] found associations between age, education levels (including paternal) and high BMI with all the dimensions of the MPSS. This may be due to sample size differences (167 vs. 406) or the specificity of the population of the study (Spanish-speaking women).…”
Section: Discussioncontrasting
confidence: 99%
“…As this shows, those three items were most likely not working well and even hindering the reliability of the subscale they were part of. This may be taken into consideration when using the scale looking for an association between variables associated with postpartum stress [3]. Thus, as this is caused by low communality on these items, recommendations made by other authors were followed [29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations